Case report: A novel 10.8-kb deletion identified in the β-globin gene through the long-read sequencing technology in a Chinese family with abnormal hemoglobin testing results - Shao, Mingkun; Wan, Yaoyao; Cao, Weipeng; Yang, Juan; Cui, Di; Ma, Minhui; Hu, Wanqin (Frontiers in Medicine, 2023)
Background: Thalassemia is a common inherited hemoglobin disorder, caused by defective of one or more globin subunits. Substitution variants and deletions in the HBB gene are the major causes of β-thalassemia, of which large fragment deletions are rare and difficult to detect by conventional polymerase chain reaction (PCR)-based methods. Case report: In this study, we reported a 26-year-old Han Chinese men, whose routine blood parameters were found to be abnormal. Hemoglobin testing were performed in the proband and his family members, of which only the proband’s mother had normal parameters. The comprehensive analysis of thalassemia alleles (CATSA, a long-read sequencing-based approach) was performed to identify the causative variants. And we finally found a novel 10.8-kb deletion including the β-globin (HBB) gene (Chr11:5216601-5227407, GRch38/hg38) of the proband and his father and brother, which were consistent with their hemoglobin testing results. The copy number and exact breakpoints of the deletion were confirmed by multiplex ligation-dependent probe amplification (MLPA) and gap-polymerase chain reaction (Gap-PCR) as well as Sanger sequencing, respectively. Conclusion: With this novel large deletion found in the HBB gene in China, we expand the genotype spectrum of β-thalassemia and show the advantages of long-read sequencing (LRS) for comprehensive and precise detection of thalassemia variants.